Relational Coherence, Speaker Preference, and Rule-Following: A Replication and Extension of Bianchi et al. (2021). - Bianchi, Paulo Henrique; Perez, William Ferreira; Harte, Colin; Barnes-Holmes, Dermot; Silva, Antonio Teixeira e (Psychological Record, 2025)
The present study evaluated the influence of relational coherence upon speaker preference and subsequent rule-following behavior. Across two experiments, participants first learned a particular set of conditional relations via a stimulus-pairing procedure (e.g., A1B1, A2B2). Then, the same relations were presented in an MTS task to ensure that participants could correctly match these stimuli. Next, the participants were exposed to two animated characters or speakers that differed by the color of their t-shirt (green or purple). One of the speakers "stated" relations that cohered (e.g., A1B1, A2B2) with the participant's previous relational training and the other stated relations that were incoherent (e.g., A1B2, A2B1). The stimulus relations were presented inside a speech balloon, as if each speaker spoke them. Rule-following was assessed during a subsequent preference test in which participants were exposed to a simultaneous discrimination task with novel stimuli. On each trial, participants first chose which of the two speakers to provide an instruction to tell them how to respond on that trial. Both speakers presented rules that were consistent with the programed contingency. In Experiment 1, feedback during the rule-following task was delivered in CRF; In Experiment 2, the schedule was FR10. In both experiments and IRAP was implemented to assess the credibility of each speaker. Results showed that a history of relational coherence with each speaker had a reliable impact upon the preference test, rule-following behaviors and the IRAP performance, irrespective of the reinforcement schedule in place (CRF in Experiment 1 and FR10 in Experiment 2).